Anakinra treatment efficacy in reduction of inflammatory biomarkers in COVID‐19 patients: A meta‐analysis. Issue 6 (18th April 2022) - Naveed, Zunaira; Sarwar, Musharraf; Ali, Zahid; Saeed, Danish; Choudhry, Khadija; Sarfraz, Azza; Sarfraz, Zouina; Felix, Miguel; Cherrez‐Ojeda, Ivan
Abstract: Introduction: Anakinra is being empirically considered for the treatment of COVID‐19 patients. The aim is to assess the efficacy of anakinra treatment on inflammatory marker reduction, including c‐reactive protein (CRP) concentrations, serum ferritin, and serum d‐dimer levels. Methods: Adhering to PRISMA 2020 statement guidelines, a systematic search was conducted across the following databases from December 2019 until January 10, 2022: PubMed/MEDLINE, Cochrane Central, Web of Science, Scopus, and EMBASE. The following keywords were employed: Anakinra, COVID*, SARS‐CoV‐2, inflammatory, CRP, D‐dimer, Ferritin, hematological, laboratory, clinical, trials. The findings were collated and presented in a tabulated manner, and statistically analyzed using Review Manger 5.4 (Cochrane). Results: In total, 2032 patients were included (881 in the anakinra and 1151 in the control/standard care group); 69.1% of them were males. Overall, the mean difference from admission until last follow‐up in CRP values was −9.66, where notable reductions were seen in the anakinra group (SMD = −0.46, p  < 0.00001, N  = 655). Serum ferritin mean values were reduced by 1467.16 in the anakinra group (SMD = −0.31, p  = 0.004, N = 537). D‐dimer mean values were largely reduced by 4.04 in the anakinra group (SMD = −0.38, p  = 0.0004, N = 375). Conclusion: This study finds that anakinra is potentially a strong candidate as an anti‐inflammatory agent to reduce mortality in COVID‐19 patients, specifically in patients with elevated inflammatory biomarkers. Abstract : Anakinra is a drug being considered for treating COVID‐19 patients. In this paper, we collate novel and pertinent findings of the mean difference in CRP values (−9.66), serum ferritin (−1467 17), and D‐dimer values (−4.04). Anakinra serves as a strong candidate particularly for its anti‐inflammatory properties in reducing mortality among COVID‐19 patients and curbing elevated inflammatory biomarkers.